Factors Affecting on Students’ Preference on Choosing Academic Track for Higher Education in Pokhara - Timilsina, Pusparaj (Kalika Journal of Multidisciplinary Studies, 2023)
The students joining higher education undergo various confusions while selecting academic track for their further studies. Students who pass the tenth grade are supposed to join the subject of their interest in grade eleven or intermediate level which will be the fundamental course for their higher education ahead. Grade eleven is the main entry point for students to establish their future in the higher education. Higher education in Nepal starts from bachelor level but students are supposed to identify their major subject starting from grade eleven. It seems that SEE graduates tend to select the major subject while joining higher education depending on various aspects like intelligence of a person, the interest towards that subject, family, peer pressure, social inputs, guidance from teachers , etc. Family (57.47%) is the major agent to assist students to take decisions for choosing the academic track while joining grade eleven. 92.52% students were not forced but 7.4% students were forced by the parents to choose the major subjects for higher education. It is surprising that 59.19% students wish to go abroad for university level education. The children joining senior high school need to be provided career guidance and counseling before choosing and handling major academic track for their higher education.